Resorbable Implants for Mandibular Fracture Fixation: A Systematic Review and Meta-Analysis. Issue 8 (August 2019) - Chocron, Yehuda; Azzi, Alain J.; Cugno, Sabrina
Abstract : Background: Mandibular fractures in adults commonly require rigid fixation to ensure proper occlusion while minimizing infection risks. Numerous centers have assessed the efficacy of resorbable materials as a potential alternative to metallic plates. The purpose of the current systematic review and meta-analysis is to shed light on overall outcomes for resorbable implants and to compare these results to those for metallic counterparts. Methods: A systematic review of clinical studies reporting outcomes for resorbable plates for mandible fractures was carried out. The reported outcomes were hardware failure/exposure, infection, wound dehiscence, reoperation, malocclusion, and nonunion. The results were pooled descriptively and stratified according to fracture and implant type. A subset meta-analysis of prospective studies comparing metallic and resorbable implants was also carried out. Results: Eighteen studies were included for a total of 455 patients managed with resorbable implants (mean follow-up, 8.95 months) with an overall complication rate of 19.8 % (n = 90/455). Infection (n = 31/455, 6.8%) and wound dehiscence (n = 28/455, 6.2%) were the most common complications. Nonunion occurred in 1.1% (n = 5/455) of patients. Seven studies were included in a meta-analysis, and the rates of adverse events in the resorbable and metallic groups were 18.0% (n = 32/178) and 18.3% (n = 33/180), respectively, with no statistically significant difference between both cohorts (95% CI 0.58, 1.82, P = 0.93). Conclusions: This study suggests that there are no statistical differences in outcomes for patients with mandible fractures managed with resorbable or metallic implants. In the absence of meta-analyses or large randomized controlled trials, the current study provides surgeons with an evidence-based reference to guide decision-making.